Du rat-toto fils du porc-épic, de la panthère et de la nandinie - Claudie Haxaire (Revue d'ethnoécologie)
The origin of the most beautiful and most complete expression of the Guro art, that of the Zamble mask and its masquerade, combine poetry of tales and precision of encyclopedic knowledge.Taking at its words the animal nicknames given by the Guro of Zuenoula to the masks of the Zamble family, namely Zamble himself, his wild brother Zàùlì and their wife Gù, we show how the habits attributed respectively to the panther, to the Gambian pouched rat and to the African palm civet, encyclopedic knowledge on which the tales are based, illuminates the warlike origin of these cults. These sacred masks being actualized in public masquerades, women whose knowledge of the sacred remains forbidden can nevertheless approach its meaning by following the naturalistic analogies that are unveiled by songs and tales. It is up to the ethnologist, woman, to acquire this knowledge to seize these bits of secrecy (its secretions, secretas in the sense of Zempleni, 1996).